Kewirausahaan sebagai Pahlawan Tanpa Tanda Bintang selama Krisis Ekonomi COVID-19: Perspektif Indonesia - Adif, Riandy Mardhika (SAFE-Network, 2022)
The COVID-19 pandemic has had a significant and catastrophic impact on businesses and the global economy. During the Covid 19 pandemic, we have identified internal and external empowerment from business creation. This study aims to provide entrepreneurial insight, implementation and dynamics to demonstrate the role of entrepreneurship in times of adversity in the Indonesian Context. The researcher provides an exploratory narrative that emerges from leading Indonesian scholars, identifying entrepreneurial initiatives for the creation and growth of new ventures. This research is in the form of insights related to the entrepreneurial mindset, the multi-dimensional effects of resilience and entrepreneurship, entrepreneurship education, entrepreneurial empowerment and ecosystem entrepreneurship. The results of this study regarding the context and empirical results. We postulate that entrepreneurship will be the unsung heroes during the current Covid-19 economic crisis.